On the inadequacy of Newswire reports for empirical research on foreign exchange interventions - Andreas Fischer (Swiss National Bank, Study Center Gerzensee, 2003)
Reuters news reports have become an accepted tool for empirical studies analyzing informational asymmetries in FX markets. This paper tests the accuracy of the Reuters reports for Swiss interventions in the foreign exchange market. The evidence finds that the time stamp of the Reuters reports does not always lie near the recorded time of the first intervention trade as is commonly assumed in market microstructure studies. The standard deviation of the time difference is measured in hours and not in minutes. These and other regression results question the accuracy of Reuters reports for Swiss interventions.
Keywords: F31; F33; 330; Central Bank Interventions; Intra-Daily Data; Reuters News Reports